Sterol C-24 Methyltransferase Type 1 Controls the Flux of Carbon into Sterol Biosynthesis in Tobacco Seed - Holmberg, Niklas (American Society of Plant Physiologists, 2002)
The first committed step in the conversion of cycloartenol into Δ(5) C24-alkyl sterols in plants is catalyzed by an S-adenosyl-methionine-dependent sterol-C24-methyltransferase type 1 (SMT1). We report the consequences of overexpressing SMT1 in tobacco (Nicotiana tabacum), under control of either the constitutive carnation etched ring virus promoter or the seed-specific Brassica napus acyl-carrier protein promoter, on sterol biosynthesis in seed tissue. Overexpression of SMT1 with either promoter increased the amount of total sterols in seed tissue by up to 44%. The sterol composition was also perturbed with levels of sitosterol increased by up to 50% and levels of isofucosterol and campesterol increased by up to 80%, whereas levels of cycloartenol and cholesterol were decreased by up to 53% and 34%, respectively. Concomitant with the enhanced SMT1 activity was an increase in endogenous 3-hydroxy-3-methylglutaryl coenzyme A reductase activity, from which one can speculate that reduced levels of cycloartenol feed back to up-regulate 3-hydroxy-3-methylglutaryl coenzyme A reductase activity and thereby control the carbon flux into sterol biosynthesis. This potential regulatory role of SMT1 in seed sterol biosynthesis is discussed.